2009
DOI: 10.1080/10790268.2009.11760749
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Intake and Body Habitus After Spinal Cord Injury: An Analysis by Sex and Level of Injury

Abstract: Background/Objectives: To examine nutrient intake and body mass index (BMI) in the spinal cord injury (SCI) population according to level of injury and sex. Design: Cross-sectional study conducted at 2 SCI treatment centers. Participants/Methods: Seventy-three community-dwelling individuals with C5-T12 ASIA Impairment Scale (AIS) A or B SCI. Subjects were divided into 4 groups: male tetraplegia (N ¼ 24), male paraplegia (N ¼ 37), female tetraplegia (N ¼ 1), and female paraplegia (N ¼ 11). Mean age was 38 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
180
2
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(192 citation statements)
references
References 39 publications
(41 reference statements)
8
180
2
2
Order By: Relevance
“…18 Both dietary fibre and calcium intakes have recently been found to be low in the SCI population. 19 Taken together, these results suggest that overall, communitydwelling adults with chronic SCI may be at increased risk for diet-related chronic conditions. There were no associations between physical activity and either overall adherence to CFG, or to most individual food groups of the Guide.…”
Section: Discussionmentioning
confidence: 78%
“…18 Both dietary fibre and calcium intakes have recently been found to be low in the SCI population. 19 Taken together, these results suggest that overall, communitydwelling adults with chronic SCI may be at increased risk for diet-related chronic conditions. There were no associations between physical activity and either overall adherence to CFG, or to most individual food groups of the Guide.…”
Section: Discussionmentioning
confidence: 78%
“…[17][18][19][20][21][22] Another factor is the hesitancy of individuals with SCI to embrace the importance of starting a longterm lifestyle changes that result in significant adaptations such as reduction in fat mass and improvement in metabolic profile. 23,24 Others have shown that dietary control is an effective strategy for prevention of obesity among individuals with SCI. 23 However, many individuals with SCI rely on meals that are high in fat and low in protein.…”
mentioning
confidence: 99%
“…We should acknowledge that persons with SCI consume close to 40% of their dietary intake as fat; which is likely to be a major source of the continuous and longitudinal changes in body FM [9,28] . This is accompanied with low consumption (less than 20%) of dietary protein intake [9,47] . Dietary intake can be manipulated to enable more effective utilization of macronutrients [47] .…”
Section: Discussionmentioning
confidence: 99%
“…This is accompanied with low consumption (less than 20%) of dietary protein intake [9,47] . Dietary intake can be manipulated to enable more effective utilization of macronutrients [47] . The American diet is especially prone to consume excessive carbohydrates and fats which alter blood glucose levels and increase adipose tissue if not expended.…”
Section: Discussionmentioning
confidence: 99%